Formation of a new conceptual model of innovative development of youth entrepreneurship in the region - O. Boris; R. Ustaev; A. Nikulina (Вестник Северо-Кавказского федерального университета, 2022)
The purpose of the development is to present the concept of a new model of innovative development of youth entrepreneurship in Russia, which will enable young people to receive the necessary support in creating and sustainable business development, and society to direct the energy and efforts of the younger generation to solve important tasks for them. To achieve this goal, the existing models of support for young entrepreneurs in Russia and abroad are considered, a verbal and graphical representation of the «digital mentoring» model is given, with all the advantages of such a conceptually new version of the model and a reflection of the issues of institutionalization of the digital support body for youth entrepreneurship, the main elements of the model are highlighted and the interrelationships between them are shown. The high relevance of testing a new model on the basis of the North Caucasus Federal District with the highest proportion of youth unemployment and the need to activate the innovative development of the district is shown.